Global pattern of nest predation is disrupted by climate change in shorebirds - Kubelka, Vojtěch; Šálek, Miroslav; Tomkovich, Pavel; Végvári, Zsolt; Freckleton, Robert P.; Székely, Tamás (Science, 2018)
No longer a safe haven Many biological patterns have a latitudinal component. One long-recognized pattern is that predation rates are higher at lower latitudes. This may explain why many migratory birds travel thousands of miles from the tropics to the poles to breed. Looking across thousands of records, Kubelka et al. found that climate change seems to have altered this fundamental pattern. In shorebirds, at least, predation rates on nests are now higher in the Arctic than in the tropics. Science , this issue p. 680